P283 An elevated PEF/FVC ratio is a marker for ILD and is associated with traction bronchiectasis on ct scan imaging. (15th November 2016) - Cranstone, K; Briggs, J; Park, J; Nicholson, T; Unstead, M
Abstract : Introduction: ILD is physiologically characterised by restrictive ventilatory pattern, impaired gas exchange, maintained airway patency and increased elastic lung recoil pressure. Spirometric values are often well-preserved but the shape of the flow volume (FVL) can suggest enhanced mechanical emptying of the lungs. Previously spirometry has identified upper airways obstruction, 1 but limited data exists for the use of an index to describe possible ILD. Method: Retrospective PFT data was analysed (n = 119). The slope of the line from PEF to RV (PEF/FVC ratio) was calculated and correlated against other PFT variables. Pearson's correlation was applied between the ratio and markers of ILD, data from table previously presented at the ARPT conference 2015*. 30 patients (27♂, 3♀) were selected for CT analysis and qualitative verification of Traction Bronchiectasis (TBX). CT scan had to be within 6 months of PFTs, FVC >70% predicted and a PEF/FVC > 2.0 (range 2.11–4.36). Information on location within the lung and level of severity was obtained. Results: Of the 30 patients, 27 were found to have TBX, (3 mild, 17 moderate and 8 severe), 3 patients had no evidence of TBX. No correlation was found between magnitude of PEF/FVC and severity of TBX. Conclusion: Structural changes from TBX may cause stenting of the airways from fibrotic tissue, holding them open during forced expiration. 2 Our volume corrected PEF/FVC predicts reduced TLC and RV percent predicted, indicating reduced lung volumes and lung stiffness in patients with restrictive lung disease. The evidence of TBX on CT imaging supports the hypothesis that airways are held open during forced expiration, allowing increased efficiency of lung emptying in patients with a PEF/FVC >2.0. The magnitude of the ratio did not correlate with TBX severity but further work to determine a cut off ratio to predict future fibrosis is required. This index may be of use indicate a value beyond which TBX is likely to be present. Reference: Empey DW. Assessment of upper airway obstruction. BMJ 1972;3 :503–505. Woodring JH, Barrett PA, Rehm SR, et al . Acquired tracheomegaly in adults as a complication of diffuse pulmonary fibrosis. AJR 1989;152 (4):743–747.